2022
DOI: 10.1155/2022/6642603
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Car Sickness of Passengers Traveled by Vehicles in North Shewa Zone, Oromia, Ethiopia

Abstract: Introduction. Car sickness is the state of being unhealthy as a result of motions that occur while traveling by vehicles. Passengers traveled by vehicles had experienced car sickness not only as a result of the biological effects but also other associated factors. Therefore, this study aimed to identify sociocultural, individual behavioral factors and situational factors resulting in car sickness of passengers traveling by minibus or bus or both. Methods. This study was designed in a cross-sectional study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Gender disparities in social relationships in tapestries have caused inconsistency between males and females who feel illness while travelling by minibuses. In line with prior research [7,15,19], this study revealed that female passengers felt more ill than male passengers. All of the research listed above did not precisely define the categories of vehicles, whether small or large.…”
Section: Findings In Relation To Understanding Passengers Feeling Unwellsupporting
confidence: 89%
See 3 more Smart Citations
“…Gender disparities in social relationships in tapestries have caused inconsistency between males and females who feel illness while travelling by minibuses. In line with prior research [7,15,19], this study revealed that female passengers felt more ill than male passengers. All of the research listed above did not precisely define the categories of vehicles, whether small or large.…”
Section: Findings In Relation To Understanding Passengers Feeling Unwellsupporting
confidence: 89%
“…The role-set impact was a significant variable in explaining how and why individuals felt ill while travelling. This study is a continuation of earlier study undertaken in the same research area [7]. Merton (1957) defines a role as "issues such as duties, responsibilities, behaviours, or expectations that a person occupies in society owing to them either through ascribed or achieved efforts. "…”
Section: Findings In Relation To Socio-cultural Factors and Feeling U...mentioning
confidence: 84%
See 2 more Smart Citations
“…Long-distance travel in an overloaded vehicle without an efficient ventilation system increases the chance of exposure to foul air and the possibility of unpleasant feelings, discomfort, headaches, and sweating (cold) symptoms of MS [ 172 ]. The administration of fresh airflow has been described as a successful technique to alleviate MS symptoms [ 129 ].…”
Section: Interventions For Mitigating Motion Sicknessmentioning
confidence: 99%